GO NATURAL, SAY NO TO CHEMICALS - A SYSTEMATIC REVIEW ON EFFECTIVENESS OF GREEN TEA EXTRACT CONTAINING FORMULATIONS ON DENTAL CARIES - PRABAKAR, JAYASHRI; JOHN, JOSEPH; ARUMUGHAM I, MEIGNANA; KUMAR R, PRADEEP; D, SRISAKTHI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: In recent years, the side effects encountered with the use of chemicals has led to the search for safe anticariogenic alternatives. Green tea is one such naturally occurring alternative which possesses anticariogenic activity through a direct bactericidal effect against cariogenic microorganisms. Therefore, the objective of this systematic review was to analyze the existing literature on the effectiveness of green tea extract containing formulations on dental caries. Methods: The databases of PubMed, Cochrane, Science Direct, Metapress, and Google Scholar were searched up to July 2015 for the related topic. References of the selected articles and relevant reviews were searched for any missed publications. Results: The systematic search revealed a total of 437 publications which were scrutinized based on eligibility criteria. Six publications fulfilled the criteria and 431 publications were excluded from the review. Out of six studies, three studies reported a statistically significant difference in favor of green tea while two studies showed no statistically significant difference between the groups. One study reported no statistically significant difference between the two groups; however, the reduction observed in chlorhexidine (control group) was slightly greater than green tea. Conclusion: With the available evidence, it can be concluded that green tea extract containing formulations are effective in reducing cariogenic microflora and caries increment.